News spillovers from the Greek debt crisis: Impact on the Eurozone financial sector - Bhanot, Karan; Burns, Natasha; Hunter, Delroy; Williams, Michael (Journal of Banking & Finance, 2014)
We examine the impact of changes in Greek sovereign yield spreads on abnormal returns of financial sector stocks for a sample of Eurozone countries, during the Greek debt crisis. We find that increases in yield spreads are associated with negative abnormal returns on financial stocks in the Portugal, Spain and Netherlands. These abnormal returns are driven in part by ratings downgrades and other unfavorable news announcements about Greece. We isolate the effects of known transmission channels–impairment of financial firms’ asset base due to cross-holdings of Greek bonds, from increases in domestic interest rates and higher funding costs. Our analysis indicates that news events lead to spillovers in excess of what can be explained by these channels of transmission.